Do really the audience's views efficiently boost built heritage conservation policies? - Jasim, Mohammed; Hanks, Laura; Borsi, Katharina (Athens Institute for Education and Research, 2017)
The role of the audience in re-manufacturing built heritage sites and formulating their conservation policies has often been outlawed by the full control of the site authority through its singularity in formulating these policies. Excluding the locals from efficient participation in setting up these policies is usually attributed by the authority to the vague role that they would precisely play. However, the rich body of ICOMOS Charters and UNESCO Conventions has frequently considered the locals as “real custodians” of these sites, legitimising their participation in drawing up heritage conservation policies. This is due to the diverse cultural potential that can be made by them for the conservation policies of these sites. This paper investigates the precise role that the audience can demonstrate within re-manufacturing heritage and constructing its futuristic policies. It is indicated that the audience‟s views possess different motives culturally, historically and touristically that enable them to efficiently participate in re-manufacturing the architectural heritage of their traditional environments. Therefore, the public‟s deep experience towards their heritage issues can revive the site with some practical ideas stemming from its reality.